Epidemiological spreading of mortgage default - Jochen Schweikert; Markus Höchstötter (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2018)
This paper introduces mathematical models to capture the spreading of epidemics to explain the expansion of mortgage default events in the United States. Here we use the state of infectiousness and death to represent the subsequent steps of payment delinquency and default, respectively. Since the local economic structure influences regional unemployment that is a strong driver of mortgage default, we model interdependencies of regional mortgage default rates through employment conditions as well as vicinity. Based on a large sample between 2000 and 2014 of loan-level data, the estimation of key parameters of the model is proposed. The model's forecast accuracy shows an above average performance compared to well-known approaches like linear regression or logit models. The key findings may be useful in understanding the dynamics of mortgage defaults and its spatial spreading.
urn:nbn:de:swb:90-798834
Keywords: R30; 330; Mortgage default; Epidemics; Spatial spreading